Faktor Penghambat Perkembangan Intelektual Anak Di Sekolah Dasar - Risma Yulianty; Anindyajati Dharmesti; Dheliana Suwardi; Mar'atus Sholihah (Indonesian Journal of Elementary and Childhood Education, 2022)
This study uses qualitative research. The purpose of this study is to find out what factors hinder the development of children at primary school age. This study used interview and observation techniques with two primary school teachers and grade 1 students. The qualitative method was chosen because it has relevant results. The results of interviews with teachers get the result that there are students who experience obstacles in the learning process. The results of interviews with students are that there are internal and external factors that hinder intellectual development. Students who experience intellectual development difficulties will have an impact on the power of thought and emotion in students. So that the quality of learning outcomes obtained will decrease. Inhibiting factors can come from the student himself (internal), as well as lack of motivation to learn. External factors also have an effect where the assistance of parents and teachers is so that the child becomes easy to accept the material. Other factors also influence the development of children's learning, namely intellectual property. Children with high abilities certainly make learning easier so that their achievements are also high.